Expression Profiles of Differentially Expressed Circular RNAs and circRNA–miRNA–mRNA Regulatory Networks in SH-SY5Y Cells Infected with Coxsackievirus B5 - Jing Li; Heng Yang; Huaran Shi; Jihong Zhang; Wei Chen (International Journal of Genomics)
Coxsackievirus B5 (CVB5) is the causative agent of hand, foot, and mouth disease (HFMD) that can cause neurological complications and fatalities. Circular RNA (circRNA) has been shown to play an important role in regulating pathogenic processes. However, the functions of circRNA in response to CVB5 infection remain unclear. In our research, RNA-seq was employed to analyze the expression profiles of circRNAs in SH-SY5Y cells with or without CVB5 infection. Out of 5,665 circRNAs identified to be expressed in SH-SY5Y cells, 163 circRNAs were found to be differentially expressed significantly. Moreover, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses showed that the differentially expressed circRNAs were mainly involved in ubiquitin-mediated proteolysis and signaling pathways during CVB5 infection. Additionally, RT-qPCR was used to validate the RNA-seq data, and a circRNA–miRNA–mRNA interaction network was constructed based on two circRNAs, such as hsa_circ_0008378 and novel_circ_0014617, which were associated with the regulation of innate immune response in host cells. Additionally, we confirmed the two circRANs up-regulated the key factors in the IFN-I signaling pathway, hampering viral replication. Our data provide a new perspective that facilitates further understanding of the virus-host mechanism.